2006 IEEE/RSJ International Conference on Intelligent Robots and Systems 2006
DOI: 10.1109/iros.2006.282357
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Networked Robotic System for Disaster Mitigation, -Navigation System based on 3D Geometry Acquisition

Abstract: Abstract-In this paper the authors present the current progress of a networked robotic system intented to be deployed at disaster areas. This system is formed by three mobile robots: two twin crawlers that will have search-and-recognition tasks gathering information about their surroundings, and an outdoorwheeled rover that will approach the area and which will also carry the two crawlers. The communication system for these robots consists of a wireless local area network that will have an operator located at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…The assumed concept is that since the HOKUYO sensor is 2D laser rangefinder, it is needed to add one more axis to provide 3D scanning. The most common way is adding a rotating mechanism in an axis different from that of the rangefinder scanning axis [3,4,5].…”
Section: Range Sensor and Common Scanning Methodsmentioning
confidence: 99%
“…The assumed concept is that since the HOKUYO sensor is 2D laser rangefinder, it is needed to add one more axis to provide 3D scanning. The most common way is adding a rotating mechanism in an axis different from that of the rangefinder scanning axis [3,4,5].…”
Section: Range Sensor and Common Scanning Methodsmentioning
confidence: 99%
“…Vargas and his colleagues [3] constructed three cooperative mobile robots capable of detecting casualties in disasters. From another perspective, Birk and his colleagues [4] developed a rescue robot to examine a collapsing building in city areas and find victims.…”
Section: B Related Workmentioning
confidence: 99%
“…Vargas et al considered fitting a large, wheeled robot with a long ramp to carry a smaller tracked robot [26]. They suggested that the robots could be fitted with wireless LAN (local area network) cameras and laser range finders for remote control.…”
Section: Introductionmentioning
confidence: 99%